1999
DOI: 10.1146/annurev.physiol.61.1.809
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hair Cell Tuning

Abstract: Mechanosensory hair cells of the vertebrate inner ear contribute to acoustic tuning through feedback processes involving voltage-gated channels in the basolateral membrane and mechanotransduction channels in the apical hair bundle. The specific number and kinetics of calcium-activated (BK) potassium channels determine the resonant frequency of electrically tuned hair cells. Kinetic variation among BK channels may arise through alternative splicing of slo gene mRNA and combination with modulatory beta subunits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
327
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(347 citation statements)
references
References 139 publications
5
327
0
2
Order By: Relevance
“…Previous studies by Rohmann and Bass (2011) and Rohmann et al (2013) showed that the seasonal variation in the frequency sensitivity of saccular hair cells in type I males could be explained by seasonal changes in the abundance of calcium-activated potassium BK channels, which are known to be responsible for a large conductance, outward current that produces electrical receptor oscillations along the hair cell epithelium (Lewis and Hudspeth 1983;Roberts et al 1988;Fettiplace and Fuchs 1999). The electrical resonance that arises from the ion-channel current kinetics of hair cells is thought to be the major contributing factor that influences low-frequency (<1 kHz) hair cell tuning in reptiles and birds (Fettiplace and Fuchs 1999) and in fish Romero 1991, 1992). Rohmann et al (2013) showed that by using the BK channel antagonist iberiotoxin to reduce BK channel availability they could effectively induce a saccular neurophysiological phenotype similar to that found in non-reproductive type I males.…”
Section: Potential Mechanisms For the Plasticity Of Saccular Sensitivitymentioning
confidence: 99%
“…Previous studies by Rohmann and Bass (2011) and Rohmann et al (2013) showed that the seasonal variation in the frequency sensitivity of saccular hair cells in type I males could be explained by seasonal changes in the abundance of calcium-activated potassium BK channels, which are known to be responsible for a large conductance, outward current that produces electrical receptor oscillations along the hair cell epithelium (Lewis and Hudspeth 1983;Roberts et al 1988;Fettiplace and Fuchs 1999). The electrical resonance that arises from the ion-channel current kinetics of hair cells is thought to be the major contributing factor that influences low-frequency (<1 kHz) hair cell tuning in reptiles and birds (Fettiplace and Fuchs 1999) and in fish Romero 1991, 1992). Rohmann et al (2013) showed that by using the BK channel antagonist iberiotoxin to reduce BK channel availability they could effectively induce a saccular neurophysiological phenotype similar to that found in non-reproductive type I males.…”
Section: Potential Mechanisms For the Plasticity Of Saccular Sensitivitymentioning
confidence: 99%
“…Soma lengths of mammalian outer hair cells (Bohne and Carr, 1985;Fettiplace and Fuchs, 1999), goldfish saccular hair cells (Sugihara and Furukawa, 1989) and frog AP hair cells (Simmons et al, 1994) decrease systematically with increasing frequency sensitivity along the auditory organ's tonotopic axis. Experiments with isolated frog AP hair cells demonstrate that whole-cell capacitances vary predictably with soma length, providing additional evidence that the hair cell's resonant frequency is inversely related to its length (Smotherman and Narins, 1999a, b).…”
Section: Introductionmentioning
confidence: 96%
“…Experiments with isolated frog AP hair cells demonstrate that whole-cell capacitances vary predictably with soma length, providing additional evidence that the hair cell's resonant frequency is inversely related to its length (Smotherman and Narins, 1999a, b). Bundle heights also negatively correlate with the frequency of maximal hair cell sensitivity in the mammalian cochlea (Lim, 1980;Fettiplace and Fuchs, 1999), and chick (Tilney and Saunders, 1983) and lizard basilar papillae (Mulroy, 1974;Turner et al, 1981).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations